Access–usage qualities of information technology in higher education setting - Manduna, Watson Moffat (Journal of Psychology in Africa, 2014)
This study examined access and usage qualities as perceived by students of Information Communication Technologies (ICT) at a South African technology university. Participants were 40 randomly selected first-year (n = 20) and secondyear (n = 20) students with an average age of 23 years. There were 13 female first year students and 12 female second year students. They responded to a brief survey on aspects of ICT availability and utilisation on campus. The data were descriptively analysed. Findings suggest ICT access to be influenced by cost, ownership and usage by individual interest.
Published Article
Keywords: accessibility; availability; Information Communication Technology; evaluative learning; resources